PENGARUH SISTEM PERPAJAKAN, TINGKAT KEPERCAYAAN, DAN HAK LEGAL TERHADAP KEPATUHAN PAJAK(TAX COMPLIANCE) (SURVEI TERHADAP UMKM DI KABUPATEN KUANTAN SINGINGI) - Wijaya, Frianti; Yusralaini, Yusralaini; Rusli, Rusli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study aimed to examine the effect of taxation system, the level of trust, and legal rights to MSMEs tax compliance in Kuantan Singingi Regency. The independent variables used in this study are the taxation system, the level of trust, and legal rights, and the dependent variable is tax compliance. The sample in this study were individual MSME registered in the Office of Cooperatives, Small, Medium, Trade and Industry in Kuantan Singingi Regency. Collecting data was conducted by questionnaire distributed directly to 88 respondents selected used convenience sampling method. The data analysis was performed using multiple linear regression analysis by SPSS version 17. The results of this study showed that simultaneously, the taxation system, the level of trust, and legal rights affect the tax compliance with a value of Fcount> Ftable (29,378 > 2,71). The partial test showed that: (1) the taxation system have a significant effect on tax compliance with a significance level of 0.003, (2) the level of trust do not have a significant effect on tax compliance with a significance level of 0.397, and (3) the legal rights have a significant effect on tax compliance with a significance level of 0,000. The magnitude of R 2 is 0,495, it is mean that the independent variables can explain the dependent variable 49.5%, while the remaining 50.5% is the effect of other variables not examined in this study.Keywords : Taxation System, Level of Trust, Legal Rights, and Tax Compliance.